Advanced methods for measuring the nutritional content of grass: integrated TaurusWebs and spectrum analysis (Research, Society and Development, 2025)
This research aimed to evaluate the effectiveness of advanced methods, specifically the integration of TaurusWebs and spectral analysis, for the accurate measurement of grass nutrient content. Ten soil and grass samples, specifically of the Megathyrsus maximus species, including the common Savoy variety and the Mombasa cv., were collected from an experimental grass crop at the coastal region of Ecuador. Samples were analyzed for total organic carbon (using a BIOBASE elemental analyzer) and protein levels (via standard lab methods). Multispectral drone images (Mavic Air 2S and RedEdge P) were also captured to generate orthomosaics and calculate NDVI, and measure chlorophyll content with an OPTI-SCIENCES CCM-200 device. TaurusWebs software provided real-time digital bromatological analysis. Statistical analysis, including Pearson correlations and Student's T-tests, was performed using Python. Findings indicate a strong correlation between organic matter and grass protein content (r=0.87), suggesting its predictive value for nutritional quality. Conversely, NDVI showed a very low correlation with protein (r=0.04) but a strong link with chlorophyll. Although TaurusWebs protein levels were somewhat lower than laboratory results, the variations were negligible and most likely caused by environmental factors or model constraints with new grass kinds.  With all factors considered, the combined method showed potential for locating and classifying regions with greater grass protein concentrations, nearly matching conventional laboratory testing.  This demonstrates the prospective contribution of cutting-edge techniques to better forage evaluation and animal production optimization.